A population-based retrospective study comparing cancer mortality between Moluccan migrants and the general Dutch population: equal risk 65 years after immigration?. Issue 8 (14th August 2019) - van der Wal, Junus M.; Bodewes, Adee; Agyemang, Charles; Kunst, Anton
Abstract : Objective: To test the hypothesis that cancer mortality rates among the Moluccan–Dutch, the oldest non-Western migrant group to arrive in the Netherlands after the Second World War, are similar to those in the general Dutch population. Design: Population-based retrospective study. Setting: Data from the national cause of death registry in the Netherlands and municipal registries. Participants: Using historic records containing family names of all Moluccan–Dutch who arrived in the Netherlands in 1951, we identified 81 591 Moluccan–Dutch persons in the national cause of death registry of the Netherlands. The reference group consisted of 15 866 538 persons of the general Dutch population. Outcome measures: Mortality data were linked to demographic data from municipal registries. We calculated all-cancer and cancer-specific mortality and measured differences between the two groups using Poisson regression, adjusting for sex, age and area socioeconomic status. We conducted a sub-analysis for the first-generation and second-generation Moluccan–Dutch. Results: There was no difference in all-cancer mortality between Moluccan–Dutch and the general Dutch population. Mortality was higher among Moluccan–Dutch for liver, cervix and corpus uteri cancers, but lower for stomach, oesophagus, kidney and nervous system cancers. For most cancers, mortality risk as compared with the general Dutch population varied between different generations of Moluccan–Dutch. Conclusions: Several decades after migration, the Moluccan–Dutch show similar all-cancer mortality, but different cancer-specific mortality rates, when compared with the general Dutch population.